Binding to F-actin guides cadherin cluster assembly, stability, and movement - Hong, Soonjin (The Rockefeller University Press, 2013)
The cadherin extracellular region produces intercellular adhesion clusters through trans- and cis-intercadherin bonds, and the intracellular region connects these clusters to the cytoskeleton. To elucidate the interdependence of these binding events, cadherin adhesion was reconstructed from the minimal number of structural elements. F-actin–uncoupled adhesive clusters displayed high instability and random motion. Their assembly required a cadherin cis-binding interface. Coupling these clusters with F-actin through an α-catenin actin-binding domain (αABD) dramatically extended cluster lifetime and conferred direction to cluster motility. In addition, αABD partially lifted the requirement for the cis-interface for cluster assembly. Even more dramatic enhancement of cadherin clustering was observed if αABD was joined with cadherin through a flexible linker or if it was replaced with an actin-binding domain of utrophin. These data present direct evidence that binding to F-actin stabilizes cadherin clusters and cooperates with the cis-interface in cadherin clustering. Such cooperation apparently synchronizes extracellular and intracellular binding events in the process of adherens junction assembly.